2017
DOI: 10.1016/j.applthermaleng.2016.09.099
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of thermal design and geometrical parameters of a flat tube-fin adsorbent bed for automobile air-conditioning

Abstract: Adsorbent bed design and performance strongly affect the overall performance of adsorption systems. In the present study, an analytical model was developed to determine the optimum geometrical and thermal parameters of a flat tube-fin adsorbent bed to reach the maximum system performance. This types of heat exchangers offer substantial reduced in weight, cost, volume and thermal conductivity, which can make them a good choice for adsorbent beds in automobile applications. Results showed that the overall therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The results of their research showed that louvered fin had the highest heat transfer rate in comparison to the other types of fins while its air side pressure drop increased very significantly compared with the plain fin. Verde et al 29 conducted optimization of geometrical parameters of a flat tube fin used in an automotive air-conditioning system. They showed that a decrease in tube thickness and fin pitch results in enhancement of cooling capacity of the radiator as well as when fin thickness and water channel wall thickness increases.…”
Section: Introductionmentioning
confidence: 99%
“…The results of their research showed that louvered fin had the highest heat transfer rate in comparison to the other types of fins while its air side pressure drop increased very significantly compared with the plain fin. Verde et al 29 conducted optimization of geometrical parameters of a flat tube fin used in an automotive air-conditioning system. They showed that a decrease in tube thickness and fin pitch results in enhancement of cooling capacity of the radiator as well as when fin thickness and water channel wall thickness increases.…”
Section: Introductionmentioning
confidence: 99%
“…However, the last method is the most important from the point of view of this paper. Heat conduction through the adsorbent has a crucial impact on the overall thermal resistance of the bed [47]. An improvement in this property without a significant deterioration of the sorption capacity will result in a much better heat exchange in the bed and, consequently, in an increase in the rate of adsorption and desorption processes as well as in an increase in the specific cooling power (SCP) [18,31].…”
Section: Introductionmentioning
confidence: 99%
“…They checked e.g., the effect of copper powders on the thermal conductivity of a mixture with activated carbon, and an increase in thermal conductivity in the range of 2 to 25% was achieved [31]. Improved heat transfer is also achieved by mixing a sorbent with a metal foam [47]. In their paper, Demir et al presented the results of a study on improving heat transfer in a bed by adding pieces of metal to silica gel.…”
Section: Introductionmentioning
confidence: 99%
“…This allows a better assessment of the system's optimal overall performance, and a better understanding of its components dynamics, as well as its performance in different locations/climates. The optimization study and assessment are an important step to evaluate the viability of adsorption systems, as several adsorption systems studies have already pointed out: cooling systems [13][14][15][16][17][18][19], heating and cooling hybrid systems [20,21], thermal heat storage systems [22][23][24][25], and desalination systems [26,27].…”
Section: Introductionmentioning
confidence: 99%